La estrategia metodológica de Platón en la primeira parte del Teeteto - Marcos de Pinotti, Graciela Elena (Revista Archai, 2015)
This article proposes to interpret Plato’s discussion on knowledge in the first part of the Theaetetus in the light of the hypothetical procedure used in the previous dialogues. The author focus on the connection between the mobilism and the definition of knowledge as sensation and tries to show that the method Plato is following is similar to the one used in the Meno in order to solve the issue of the teachability of virtue. Theaetetus and Meno are closely related not only by their method. Both are in relation with the early, Socratic, dialogues, and at the same time are crucial for interpreting those that follow them.